Mosquito-Specific Viruses—Transmission and Interaction - Eric Agboli; Mayke Leggewie; Mine Altinli; Esther Schnettler (Viruses, 2019)
Mosquito-specific viruses (MSVs) are a subset of insect-specific viruses that are found to infect mosquitoes or mosquito derived cells. There has been an increase in discoveries of novel MSVs in recent years. This has expanded our understanding of viral diversity and evolution but has also sparked questions concerning the transmission of these viruses and interactions with their hosts and its microbiome. In fact, there is already evidence that MSVs interact with the immune system of their host. This is especially interesting, since mosquitoes can be infected with both MSVs and arthropod-borne (arbo) viruses of public health concern. In this review, we give an update on the different MSVs discovered so far and describe current data on their transmission and interaction with the mosquito immune system as well as the effect MSVs could have on an arboviruses-co-infection. Lastly, we discuss potential uses of these viruses, including vector and transmission control.